2010
DOI: 10.1021/la103655x
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Salt Trend from Soft to Stiff in Single Neurofilament Biopolymers

Abstract: We present persistence length measurements on neurofilaments (NFs), an intermediate filament with protruding side arms, of the neuronal cytoskeleton. Tapping mode atomic force microscopy enabled us to visualize and trace at subpixel resolution photoimmobilized NFs, assembled at various subunit protein ratios, thereby modifying the side-arm length and chain density charge distribution. We show that specific polyampholyte sequences of the side arms can form salt-switchable intrafilament attractions that compete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…The main difference between native NFs (with contour length on the order of a few microns 10 ) and reconstituted NFs is that the latter have a shorter contour length of E200 nm (ref. 37). Thus, although the single-molecule properties between NFs with small and long contour lengths will be different, we expect that the shorter contour length should not lead to significantly different properties (both microscopic and macroscopic) of the extended NF network hydrogels compared to networks consisting of longer native filaments.…”
Section: Methodsmentioning
confidence: 90%
“…The main difference between native NFs (with contour length on the order of a few microns 10 ) and reconstituted NFs is that the latter have a shorter contour length of E200 nm (ref. 37). Thus, although the single-molecule properties between NFs with small and long contour lengths will be different, we expect that the shorter contour length should not lead to significantly different properties (both microscopic and macroscopic) of the extended NF network hydrogels compared to networks consisting of longer native filaments.…”
Section: Methodsmentioning
confidence: 90%
“…This review describes experiments on reconstituted NF hydrogels, including studies in which the subunit compositions are near those found in axons and dendrites in vivo (9,(28)(29)(30)(31)(32). The ability to reconstitute NF hydrogels at different subunit compositions is essential, and together with small-angle-X-ray scattering (SAXS) and SAXS osmotic pressure techniques, allows clarification of the role of each subunit on hydrogel structure and phase behavior (which includes NF orientational flexibility) as well as on the interfilament forces related to the mechanical properties of the network (33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized for some time that the cytoskel-41 eton, a composite network of filamentous proteins, along with corre- 42 sponding linker proteins and molecular motors is a highly mobile, 43 viscoelastic and flexible entity, which determines cell mechanics to a 44 great extent [1]. Actin-based microfilaments (MFs) and tubulin-based 45 microtubules (MTs) are polar filaments and both interact directly with 46 the molecular motors myosin or kinesin and dynein, respectively.…”
mentioning
confidence: 99%